Enamel isotopes reveal late Pleistocene ecosystem dynamics in southeastern North America. (15th May 2020) - Noble, Elizabeth J.; McManus, Julia G.; Mead, Alfred J.; Mead, Heidi; Seminack, Christopher; Balco, William; Bennett, Todd; Crain, Nicole M.; Duckworth, Cory; Malasek, Taylor; Pearson, Jason Z.; Rhinehart, Parker; et al.
Abstract: The end of the late Pleistocene (∼10, 000 years ago) witnessed the extinction of over seventy percent of North America's megafaunal genera. Although this pattern has been extensively investigated, its causal mechanisms remain elusive. Much of this difficulty is related to the spatial and temporal discontinuity of sites dating to the period leading up to the extinctions. In this study, we present new stable carbon and oxygen isotope data from Mammuthus columbi and Bison latifrons teeth collected from a well-dated Last Glacial Maximum (∼20, 000 rcybp) locality called Clark Quarry in coastal Georgia, USA. This site lies in direct proximity to where Sir Charles Lyell collected the type specimen of M. columbi in 1846 and therefore is of added historical significance. We compare these data to those from similarly aged (Sangamonian interglacial and Wisconsin glacial intervals) localities from Florida and demonstrate the presence of a vegetation gradient with elevated levels of C3 vegetation at higher latitudes. Serially-sampled δ 13 C and δ 18 O values suggest that Clark Quarry Mammuthus and Bison changed their diet seasonally with the incorporation of elevated quantities of C4 vegetation during warmer periods. Our data indicate more exaggerated seasonal dietary variability in these taxa at Clark Quarry relative to those collected from the Sangamonian interglacial locality of Waccasassa River in Florida, providing additional evidence for the significant influence of glacial dynamics in structuring North American ecosystems. These high-resolution ecological patterns should be incorporated into hypotheses focused on extinction dynamics in southeastern North America and more broadly. Highlights: Isotope data from Mammuthus columbi and Bison latifrons from provide insight into late Pleistocene environments in southeastern North America. δ 13 C values from Mammuthus and Bison from indicate a vegetation gradient with elevated levels of C3 vegetation at higher latitudes. Mammuthus and Bison changed their diet seasonally with elevated quantities of C4 vegetation during warmer periods. Serially-sampled δ 18 O values indicate increased seasonality in coastal Georgia relative to Florida during the late Pleistocene.